Integrating genetics and suitability modelling to bolster climate change adaptation planning in Patagonian nothofagus forests - Marchelli, Paula (2017)
We investigated the impact of past changes in habitat suitability on the current patterns of genetic diversity of two southern beeches (Nothofagus nervosa and Nothofagus obliqua) in their eastern fragmented range in Patagonian Argentina, and model likely future threats to their population genetic structure. Our goal was to develop a spatially-explicit strategy for guiding conservation and management interventions in light of climate change. We combined suitability modelling under current, past (Last Glacial Maximum ~ 21,000 BP), and future (2050s) climatic conditions with genetic characterization data based on chloroplast DNA, isozymes, and microsatellites.We show the complementary usefulness of the distribution of chloroplast haplotypes and locally common allelic richness calculated from microsatellite data for identifying the locations of putative glacial refugia. Our findings suggest that contemporary hotspots of genetic diversity correspond to convergence zones of different expansion routes, most likely as a consequence of admixture processes. Future suitability predictions suggest that climate change might differentially affect both species. All genetically most diverse populations of N. nervosa and several of N. obliqua are located in areas that may be most severely impacted by climate change, calling for forward-looking conservation interventions. We propose a practical spatially- explicit strategy to target conservation interventions distinguishing priority populations for in situ conservation (hotspots of genetic diversity likely to remain suitable under climate change), ex situ conservation in areas where high genetic diversity overlaps with high likelihood of drastic climate change, vulnerable populations (areas expected to be negatively affected by climate change), and potential expansion areas under climate change.